Blockchain and AI in Reverse Logistics: A Qualitative Synthesis of Strategic Applications and Challenges (London Journal of Research In Management & Business, 2025)
Since the rapid growth of e-commerce, product returns volume has soared, creating  pressure on reverse logistics systems to be more efficient, transparent and cost-effective.  Nonetheless, the traditional reverse logistics processes are encountered with operational  challenges such as high costs, return fraud, ineffective tracking systems, and  environmental concerns. Mature AI and Blockchain Technologies allow businesses to  automate various processes, make more informed decisions, and ensure that supply chain  operations are transparent. Based on case studies from leading global companies including Amazon, Walmart, and  Alibaba, this study sheds light on the integration of AI and Blockchain in reverse  logistics as an avenue for reverse logistics integration in overall supply chain strategy.  Employing a qualitative methodology and secondary data sources, including industry  reports, academic literature, and company publications, this study explores how these  modern technologies are positively impacting return management processing, fraud  detection, operational efficiency, and sustainability. AI-powered automation greatly helps the companies in returns forecasting, inventory  optimization, and customer service, unveiling the time and costs relating to reverse  logistics operations as per the findings. Simultaneously, the implementation of  blockchain technology allows for real-time tracking, fraud mitigation, and generation of  trusted data for sharing, thereby enhancing return transactional transparency.  Specifically, companies which combine both AI and blockchain, directly creates use  cases leading to superior decision-making capabilities, more efficient logistics and  support processes, as well as superior management of product returns.  While these technologies offer potential advantages, the study reveals critical hurdles in  implementing these technologies, such as high deployment costs, regulatory obstacles,  data privacy issues, and interoperability challenges among various blockchain systems.  Moreover, it can also be quite challenging for companies to find the technical expertise  needed to implement AI or blockchain in their logistics infrastructure.To the best of our knowledge, this research effort contributes to the literature on supply  chain management and technology adoption by providing tested instruments and best  practice options for businesses that seek to enhance their reverse logistics operations  through the application of technologies. The study also aids theory and practice by  illustrating some policies for adoption challenges and offering managerial  recommendations for firms. These insights need to be validated and refined through  empirical research and industry application of AI and blockchain in the context of  reverse logistics (Wang et al., 2018; Kafeel et al., 2023).
Keywords: Nigeria; Cybersecurity threats; demand/supply side of financial inclusion; and OLS/2SLS/GMM; digitalization; manager; value-based orientations; formation of value-based orientations; business; Correlation; Gross Domestic Product; CO2 emissions; GLS method; STATA14; Autoregressive Lag model; coefficient of determination.; sustainability; Blockchain; E-Commerce; Reverse Logistics; Supply Chain Optimization; Returns Management; Fraud Prevention